Reforming the Pension Reforms : The Recent Initiatives and Actions on Pensions in Argentina and Chile - Rofman, Rafael; Fajnzylber, Eduardo; Herrera, German (World Bank, Washington, DC, 2014)
This paper describes the recent reforms of pension policies adopted by Argentina and Chile. The structural reforms in the 1980s and 90s were targeted on improving the long term fiscal sustainability of the system and their institutional design, while transferring part of the economic and social risks from the State to participants. However, in recent year s authorities in both countries coincided on identifying insufficient coverage among the elderly and adequacy of benefits as the most critical problems. As a result of differences in political economy and institutional constraints, responses were different. In Chile, a long and participatory process resulted in a large reform that focuses on impacts on the medium term, through a carefully calibrated adjustment. In Argentina, instead, reforms were adopted through a large number of successive normative corrections, with little public debate about their implications, and immediate impacts on coverage and fiscal demands.